AN ANALYSIS OF STUDENTS’ NEEDS AND PREFERENCES TO DEVELOP ENGLISH TEXTBOOK FOR THE SEVENTH GRADERS - Rino Thesaloga (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This paper is compiled to address the students’ needs regarding topics and material preferences in learning English also their present difficulties. The incompatibility of the current textbook is indicated by the students’ scores on multiple academic assessments. One of the main factors is that most students did not learn English in Elementary School; hence they only know a few isolated English words. As a result, they struggle to comprehend the full English content. This descriptive-quantitative research extracted the students’ bilingual status, opinions, purposes, and topic preferences from 55 students to develop a more compatible English textbook. As a result, the questionnaire and the interview show that the students want elementary-level material, accessible pronunciation examples, involvement of Bahasa Indonesia, and topics based on local content.